Insights into ZrO2- and Al2O3-based submerged entry nozzle clogging for the continuous casting of RE-treating sulfur resistant casing steel. Issue 14 (15th July 2022) - Li, G.; Tang, H.Y.; Jiang, X.Y.; Liu, J.W.; Lan, P.; Zhang, J.Q.
Abstract: The ZrO2 - and Al2 O3 -based submerged entry nozzle (SEN) clogging during continuous casting of a RE-treating sulfur resistant casing steel is studied experimentally based on morphological analysis and the related thermodynamic calculations. The results show that the ceramic cloggings exists both in the inner-wall and outlet regions of SEN, while the latter is the main reason for terminating the casting with its clogging reaching 77% in the nozzle cross section area. The clogging is caused by RE-containing inclusions from molten steel and reoxidation products by the reaction between RE in molten steel and the initial formed cloggings on nozzle refractory. The possible existence state of RE in molten steel with its content has been discussed, and the clogging mechanism studied in detail. To prevent nozzle clogging, suggestions are given for continuous casting of the RE-treating steel with a modified RE treatment strategy for less solid inclusions and solute [RE] presented in liquid steel during refining process. Additionally, the optimization of nozzle geometry and its refractory materials may help as well.